Thermal Effect Estimation of Smartphone Virtual Reality Headsets on Human Eye by Finite Element Method - Niyazi Uluaydın; Selim Şeker (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Smartphones (SP) terminals are becoming the most popular media for virtual reality (VR) and augmented reality (AR) effects with their central processing unit (CPU) and video capabilities. Simple VR headsets with reasonable costs can host smartphones, and they can together be used for many different applications. But with the outbreak of Covid-19 pandemic, their usage has become essential for many people working from their homes. VR and AR capabilities provide a much richer experience for entertainment, gaming, and video conferencing. The increasing popularity of 3D virtual worlds add up to this usage. On the technology side, multi-radio connectivity is supported both on terminal and network side. A certain risk may arise when using SP VR headsets for such applications requiring a broadband Internet connectivity. SPs with multi-radio connectivity feature may elevate specific absorption rate (SAR) values in those cases. The smartphone used for VR and AR applications is positioned in front of the eyes; and there is very limited ventilation in VR/AR headsets. Authors’ model aims simulate these exposure scenarios in 4G and 5G mobile telecommunication frequencies by finite element method (FEM); and, possible thermal and non-thermal risks of related electromagnetic (EM) radiation on human eye according to the outputs of the model are discussed.